On almost statistical convergence of generalized difference sequences of fuzzy numbers - Et, M.; Altin, Y.; Altinok, H. (Mathematical Modelling and Analysis, 2005)
The purpose of this paper is to introduce the concepts of almost statistical convergence and strongly almost convergence of generalized difference sequences of fuzzy numbers. We obtain some results related to these concepts. It is also shown that almost Δr λ ‐ statistical convergence and strongly almost Δr λ ‐ convergence are equivalent for Δr ‐ bounded sequences of fuzzy numbers.Apie beveik statistinį apibendrintų skirtuminių fuzzy skaičių sekų konvergavimąŠio straipsnio tikslas supažindinti su beveik statistinio ir stipriai beveik statistinio apibendrintų fuzzy skaičių konvergavimo sąvokomis. Straipsnyje taip pat parodyta, kad beveik Δr λ ‐ statistinis konvergavimas ir stipriai beveik Δr λ ‐ statistinis konvergavimas yra ekvivalentus Δr λ ‐ apribotoms fuzzy skaičių sekoms.First Published Online: 14 Oct 2010